Citizen Science: założenia koncepcyjne i perspektywy zastosowania w naukach o polityce - Jańczak, Jarosław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
Prezentowany tekst jest pogłębioną analizą koncepcji nauki obywatelskiej (citizen science, CS) – zaangażowania obywateli-nienaukowców w prowadzenie badań naukowych. Celem artykułu jest osadzenie paradygmatu CS w filozofii nauki i stworzenie matrycy analitycznej schematów rozumienia CS, zdefiniowanie specyfiki zastosowania nauki obywatelskiej w naukach politycznych oraz zdiagnozowanie lokalnych kontekstów stosowania CS w realizacji projektów badawczych w Polsce. Metodologicznie tekst bazuje na analizie literatury przedmiotu. Efektem rozważań jest rozwinięcie ramy koncepcyjnej w postaci siatki kategorialnej aktywności CS oraz próba zdefiniowania pozycji citizen science w naukach politycznych na tle innych dyscyplin badawczych. Analiza polskich wątków wykazała mniejszą popularność CS wynikającą z kwestii organizacyjnych i finansowych. The presented text is an in-depth analysis of the concept of citizen science (CS) – the involvement of non-academic citizens in conducting scientific research. The aim of the article is to embed the CS paradigm in the philosophy of science and create an analytical matrix of CS understanding schemes, to define the specifics of the application of citizen science in political science, and to diagnose local contexts of using CS in the implementation of research projects in Poland. The text is methodologically based on the analysis of the academic literature in the field. The result of the considerations is the development of a conceptual framework in the form of a categorical grid of CS modes and the attempt to define citizen science position in political science compared to other research disciplines. The analysis of Polish threads showed a lower popularity of CS resulting from organizational and financial constraints.
Citizen Science: Conceptual Assumptions and Prospects for Application in Political Science
Keywords: nauka obywatelska; nauki społeczne; nauki polityczne; citizen scence; innowacje w nauce; citizen science; social science; political science; innovations in science